Association of serum creatinine/cystatin C ratio with insulin resistance and all-cause mortality: a national cohort analysis - Han, Yutong; Zhang, Jiahong; Li, Qian; Wan, Bin; Xie, Chunguang (Frontiers in Nutrition, 2025)
BackgroundSerum creatinine/cystatin C (Cr/CysC), a biomarker for skeletal muscle mass, has not been well studied in relation to insulin resistance (IR). This study examined the associations between Cr/CysC, IR, and all-cause mortality.MethodsData were sourced from the NHANES database and analyzed using logistic and linear regression to assess the association between Cr/CysC and IR, quantified by the triglyceride-to-high-density lipoprotein cholesterol (TG/HDL) ratio. Restricted cubic splines (RCS) were employed to identify non-linear associations, and Cox regression was leveraged to determine associations with all-cause mortality.ResultsHigher Cr/CysC ratios were strongly associated with lower IR risk (OR = 0.48, 95% CI: 0.32–0.73, p = 0.001) and lower TG/HDL (β = −0.60, p = 0.001). RCS analysis indicated a non-linear relationship, with increased IR risk below a certain threshold (p < 0.05). Cox regression revealed a negative association between Cr/CysC and all-cause mortality in the overall population (HR = 0.47, 95% CI: 0.31–0.69, p < 0.001) and among non-IR individuals, but not among those with IR. Associations were stronger in middle-aged individuals, women, and non-hypertensive participants.ConclusionCr/CysC is inversely associated with IR and all-cause mortality, suggesting its potential as a low-cost marker for stratifying IR risk.